Speculative petroleum systems of the southern Pelotas Basin, offshore Uruguay - Conti, Bruno; Jesus Perinotto, Jose Alexandre de [UNESP]; Veroslaysky, Gerardo; Castillo, Maria Gabriela [UNESP]; Ana, Hector de Santa; Soto, Matias; Morales, Ethel (Elsevier B.V., 2017)
The Pelotas Basin of Brazil and Uruguay represents a frontier basin with under-explored hydrocarbon potential. Although oil and gas accumulations have yet to be identified, only 21 exploratory wells have been drilled in an area of more than 330,000 km(2), 20 of which are located in the Brazilian portion of the basin. A detailed study of the petroleum system of offshore Uruguay has strong potential to contribute to a better characterization of the capacity of the basin to generate and accumulate hydrocarbons. Three stages have previously been recognized during the evolution of Pelotas basin: (1) a prerift phase which preserved Paleozoic and Mesozoic units of the Parana Basin; (2) an Early Cretaceous volcano-sedimentary synrift phase; and (3) a Cretaceous to Cenozoic postrift phase deposited during the passive margin stage. In this study, we use sequence stratigraphy methodology to interpret 2D multichannel seismic sections of the southern segment of the Pelotas Basin in the Uruguayan Atlantic margin. This analysis allows us to identify depositional sequences, systems tracts and the distribution of the main elements of the potential petroleum systems. Following our analysis, we propose six speculative petroleum systems (SPS) in the Pelotas Basin. The first SPS is related to the prerift phase and is represented by a Lower Permian restricted marine source rock and reservoirs related to Permian to Upper Jurassic aeolian and fluvial sandstones. The second SPS corresponds to the synrift phase and is constituted by a Barremian lacustrine source rock with reservoirs of alluvial/fluvial sandstones of the same age. The other four proposed SPS are associated with the postrift phase, represented by marine source rocks related to Aptian-Albian, Cenomanian-Turonian and Paleocene transgressions, all of which are identified in the region and interpreted in seismic lines from Uruguay. These postrift SPS have predominantly siliciclastic reservoirs represented by Early Cretaceous aeolian sandstones and Cretaceous to Cenozoic deltaic sandstones and turbidites. (C) 2017 Elsevier Ltd. All rights reserved.
Keywords: Sequence stratigraphy; Petroleum systems; Pelotas basin; Uruguayan atlantic margin